rs2682818/MiR-618 is a novel marker associated with increased risk of breast cancer in the Iranian population - Najafian-Najafabady, Atefeh; Ebrahimi, Nasim; Vallian, Sadeq (Archives of Biological Sciences, 2021)
Paper description: micro-RNA-618 (miR-618) plays a major role in a variety of tumors, including breast cancer. rs2682818/miR-618 polymorphism in breast cancer patients and healthy individuals was genotyped to examine the association between this polymorphism and breast cancer prevalence. correlation between rs2682818/miR-618 and the risk of breast cancer is statistically significant (OR=2.97, P=0.0003). rs2682818/miR-618 could be considered as an important marker associated with the risk of breast cancer Abstract: The presence of single nucleotide variations in the coding region of micro-RNA (miRNA)-encoding genes plays a significant role in the expression and function of these molecules in oncogenesis and cancer. The association of rs2682818 in miR-618 with increased risk of breast cancer was investigated in the Iranian population. rs2682818/miR-618 was genotyped using amplification-refractory mutation system PCR (ARMS-PCR) in 200 healthy individuals and patients with breast cancer. The data revealed the presence of Hardy-Weinberg equilibrium (HWE) for this marker. The frequency of alleles C and A was 70% and 30%, respectively, in healthy individuals; the frequency of alleles C and A was 44% and 56%, respectively, in patients with breast cancer. Analysis of odd ratios showed that the rs2682818/miR-618 polymorphism is associated with increased probability of breast cancer and is statistically significant (OR=2.97, P=0.0003). The data suggest that rs2682818/miR-618 could be considered a novel marker of increased risk of breast cancer.